TRENDS IN INDUSTRIAL DEVELOPMENT IN KYRGYZSTAN IN THE EAEU CONDITIONS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
In the modern world, the competitiveness of national economies is largely determined by the state of the industrial sector, the degree of its modernization, compliance with the new technological structure, the availability of professional labor resources, etc. Regional integration interactions are also of no small importance, facilitating the “transfer” of knowledge, experience, technology, the development of new business models, etc. This publication shows the features and main trends in the development of the industrial sector of Kyrgyzstan at the present stage, and identifies problems that impede positive development.
Keywords: industry, manufacturing industry, sustainable development, green economy, foreign direct investment, light industry, gross domestic product